Time, Tense, and Modality : Proceedings of the XXIII European Symposium on Medieval Logic and Semantics - Bieniak, Magdalena; Wciórka, Wojciech (Investigating Medieval Philosophy, 2026)
This volume gathers twelve papers exploring how medieval thinkers conceptualized time, examined the linguistic expression of temporality, and addressed the impact of time's passage on the scope of possibility and necessity. Drawing on the XXIII European Symposium on Medieval Logic and Semantics, these essays also venture into natural philosophy, metaphysics, and theology, uncovering fresh arguments and revisiting pivotal debates from Avicenna through the fourteenth century. Contributors are Fabrizio Amerini, Allan Bäck, Magdalena Bieniak, Jon Bornholdt, Enrico Donato, Davide Falessi, Heine Hansen, Elżbieta Jung, Martyna Koszkało, John Marenbon, Costantino Marmo, Stephen Read, Paul Thom, Luisa Valente, and Wojciech Wciórka.